2020
DOI: 10.1136/jitc-2020-001557
|View full text |Cite
|
Sign up to set email alerts
|

Domain binding and isotype dictate the activity of anti-human OX40 antibodies

Abstract: BackgroundPrevious data suggests that anti-OX40 mAb can elicit anti-tumor effects in mice through deletion of Tregs. However, OX40 also has powerful costimulatory effects on T cells which could evoke therapeutic responses. Human trials with anti-OX40 antibodies have shown that these entities are well tolerated but to date have delivered disappointing clinical responses, indicating that the rules for the optimal use of anti-human OX40 (hOX40) antibodies is not yet fully understood. Changes to timing and dosages… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 55 publications
3
18
0
Order By: Relevance
“…Our observations regarding the influence of mAb isotype on agonism are concordant with those reported for other TNFRSF members (CD40, 4-1BB and OX40) 17 , 18 , 27 , 29 . For CD40, the m1 format, which preferentially engages FcγRIIb is highly agonistic, whereas m2a is inactive 41 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our observations regarding the influence of mAb isotype on agonism are concordant with those reported for other TNFRSF members (CD40, 4-1BB and OX40) 17 , 18 , 27 , 29 . For CD40, the m1 format, which preferentially engages FcγRIIb is highly agonistic, whereas m2a is inactive 41 .…”
Section: Discussionsupporting
confidence: 91%
“…Although it is clear that mAb isotype plays a central role in providing agonism, it is also evident that epitope location matters. Murine OX40 mAb binding to membrane-proximal epitopes mediate superior agonism over those binding more distally 28 , with similar findings for human OX40 (hOX40) mAb 29 . In contrast, for hCD40 mAb, strong agonism is observed with mAb binding to the most distal epitopes 18 .…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…However, a wealth of information has been generated on the functional requirements of agonistic mAb. For example, we previously demonstrated that the complex interplay between epitope, isotype and FcγR availability determines the agonistic activity of anti-CD40 mAbs, and similar principles are being applied to other TNFRs [7][8][9]47 . Fluorescence microscopy has shown that TNF ligands and agonistic mAbs induced TNFR clustering on the cell surface; however, the requirement for secondary crosslinking remains unresolved 46,[48][49][50] .…”
Section: Discussionmentioning
confidence: 98%
“…ostimulatory tumour necrosis factor receptors (TNFRs) play important roles in immune activation and represent promising targets for next-generation cancer immunotherapeutics [1][2][3] . Selective TNFR activation has been shown to augment antitumor immunity and confer robust therapeutic benefits in animal models 1 with TNFR-targeting mAbs and recombinant ligands showing promising antitumor activities in early phase trials 1,4,5 , although they remain behind checkpointblocking reagents in their development, likely due to a poorer understanding of how the activity is achieved and their multiple potential mechanisms of action 6,7 . These clinical candidates display a range of agonistic activities resulting from differential TNFR activation, with their level of agonism correlated positively with their pharmacodynamic properties in clinical trials [8][9][10][11][12][13] .…”
mentioning
confidence: 99%